INTELLIGENTE SALZFABRIK SELF INTEGRATED PHARMACEUTICAL RAW MATERIALS INDUSTRY IN INDONESIA - Ardhina Nugrahaeni (OISAA, 2018)
ABSTRACT Currently, Indonesia's pharmaceutical industry is still heavily dependent on imported raw materials, almost 95% of the needed medicine raw materials (BBO) still have to be imported from abroad. Based on data from the Directorate General of Foreign Trade, Ministry of Trade Republic of Indonesia, it was showed that the pharmaceutical salt import in 2013 reached 3,152 tons and all of them needed to fulfill domestic needs. This study used literary study method by collecting data or information in accordance with the topic. Geographically Indonesia consists of islands large and small number of approximately 17,504 islands. Three quarters of its territory is the ocean (5.9 million km2), with a 95,161 km long coastline, the second longest in the world after Canada. This makes Indonesia the world's largest archipelago in the world. This written idea was created as a solution to the problem of dependence on medicine raw materials import in the pharmaceutical industry of Indonesia. The solutions presented are Intelligente Salzfabrik: The Concept of Self-Integrated Pharmaceutical Raw Materials Industry which is Energy Independence and High Accessibility on Coastal with Sea Toll and Power Flow to Achieve An Imported Medicine Raw Materials Independence in Indonesia. This development will be implemented in close proximity to coastal areas near the the sea so that it can simplify both cost and transportation required for the distribution of salt produced.